Peran Literasi Keuangan Digital dalam Memoderasi Hubungan antara Persepsi Risiko dan Penggunaan E-Wallet pada Pelaku UMKM Lintas Generasi di Kabupaten Morowali - Amalia Husen , Ayu; Sastrawan Farid, Erwan; Kadang, Juliana; Anisah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the role of digital financial literacy in moderating the relationship between risk perception and e-wallet use among MSME actors across generations in Morowali Regency. Using a quantitative survey of 160 respondents analyzed with SEM-PLS and Multi-Group Analysis, the results show that risk perception negatively affects e-wallet use. Digital financial literacy significantly weakens this negative relationship, with the strongest moderating effect found in Generation Z. These findings imply that enhancing digital financial literacy is essential to reducing perceived risks and encouraging inclusive digital payment adoption among MSMEs across generational groups.